Crossbreeding Systems in Beef Cattle - Gary R. Hansen (EDIS)
AN165, a 5-page fact sheet by Gary R. Hansen, explains to beef cattle producers this breeding strategy that leads to increased performance and productivity in beef cattle herds. Published by the UF Department of Animal Science, September 2006.